Voegelin recollected conversations on a life - Cooper, Barry, 1943-; Bruhn, Jodi (Eric Voegelin Institute series in political philosophy., 2008)
"Personal recollections of Eric Voegelin by his wife, his closest friends, and his first-generation students reveal new aspects of the philosopher's personality. Reflections of people such as Paul Caringella, Bruno Schlesinger, and Heinz Barazon capture Voegelin's greatness and shortcomings alike and shed new light on his philosophical quest for truth"--Provided by publisher.